PERLINDUNGAN HUKUM TERHADAP KORBAN KEKERASAN SEKSUAL PASCA PENETAPAN UNDANG-UNDANG NOMOR 12 TAHUN 2022 TENTANG TINDAK PIDANA KEKERASAN SEKSUAL - Sinaga, Hasudungan (IBLAM LAW REVIEW, 2022)
This research is entitled legal protection of victims of sexual violence after the enactment of Law Number 12 of 2022 concerning criminal acts of sexual violence. Formulation of the problem of how the legal protection for victims of sexual violence and how the effectiveness of legal protection for victims of sexual violence after the enactment of Law Number 12 of 2022 on criminal acts of sexual violence. With normative juridical methods. Sexual violence against women and children is a serious problem in every country. In the city of Makassar, cases of sexual violence against children have increased significantly during 2021. Makassar City DPPPA recorded a surge of 302 cases in the last three years, compared to 52 cases in 2020. In 2019, the number of cases of sexual violence against children even reached 127 cases. These incidents of sexual violence are generally carried out by the closest people, with the family environment being the place where the most cases occur